Behavior Based Conceptual Model of Sharia Accounting Model: Integrating, Ethics, Intention and Sharia Compliance - Andrianto Andrianto; Imran Syah; Teguh Hadi Wibowo (Journal of Accounting Science, 2026)
General Background: Increased competition in modern business not only demands profit maximisation, but also compliance with ethical principles, where accounting plays a strategic role in ensuring moral, social, and spiritual compliance, especially within the Islamic framework. Specific Background: Islamic business ethics are based on Sharia values that emphasise justice, honesty, social responsibility, and truthfulness; however, practical business activities often reveal a gap between these principles and commercial practices, as seen in cases of fraud and ethical violations. Knowledge Gap: Previous studies have largely examined Islamic accounting from a technical and standards-based perspective, with limited attention to behavioural and ethical dimensions. Objective: This study aims to develop an Islamic accounting model that integrates behavioural aspects to achieve financial, social, and spiritual goals simultaneously. Method: Using a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and literature reviews, and analysed thematically through data reduction, classification, and interpretation. Results: Findings indicate that the application of Shariah ethical values enables fairness, honesty, social responsibility, and truthfulness to be operationalised in accounting practice through a behaviour-based conceptual model. Novelty: The novelty of this study places ethical behaviour as a fundamental element of Islamic accounting. Implications: Theoretically, this study enriches the Islamic accounting literature with behavioural insights, while practically it provides guidance for Islamic business entities and regulators in formulating transparent and fair accounting standards in accordance with Sharia values.